2016
DOI: 10.1186/s13018-016-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of serum CTX-II and COMP concentrations in osteoarthritis model rabbits: an effective technique for early diagnosis and estimation of disease severity

Abstract: BackgroundEarly diagnosis of osteoarthritis (OA) is difficult. Cartilage oligomeric matrix protein (COMP) and crosslinked C-telopeptides of type II collagen (CTX-II) are two markers which can potentially predict the destruction of articular cartilage of early OA. To comprehensively evaluate the diagnosis value of serum COMP and CTX-II markers in OA, the longitudinal and combined measurement of serum COMP and CTX-II were performed at different stages of pathological process of OA in adult rabbits with OA, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…The histological results in our study also have a corresponding experimental trend. This also shows that the articular cartilage has been obviously damaged from the second week in histology, and continued to aggravate with the passage of time, suggesting that CTX-II may also be used as a suitable biomarker for longitudinal study [28]. In addition, we used Mankin scoring system to explore the relationship between the concentration of CTX-II and the degree of articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…The histological results in our study also have a corresponding experimental trend. This also shows that the articular cartilage has been obviously damaged from the second week in histology, and continued to aggravate with the passage of time, suggesting that CTX-II may also be used as a suitable biomarker for longitudinal study [28]. In addition, we used Mankin scoring system to explore the relationship between the concentration of CTX-II and the degree of articular cartilage degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…COMP serum concentrations were negatively correlated with disease duration, and positively associated with age, physical and sports activities. 96,97 Bai et al 98 induced OA in rabbits by anterior crucial ligament transsection and monitored the evolution of s-CTX-II and COMP at baseline and weeks 2, 4, 6, 8, 10, and 12 after the intervention. The CTX-II and COMP concentrations increased gradually to week 12, in parallel with the disease severity index Mankin score.…”
Section: Collagen Type II Degradation Products and Comp As Biomarkersmentioning
confidence: 99%
“…Histological findings confirmed a slow, but progressive cartilage deterioration. 98,99 In such a design, the CTX-II/COMP combination may be a marker for early diagnosis, evolution, and disease severity. In the study of Riegger et al, 100 conducted on 754 subjects who underwent total joint replacement, serum COMP levels positively correlated with markers of renal (cystatin C, creatinine, estimated glomerular filtration rate-eGFR) and cardiac (N-terminal propeptide of brain natriuretic peptide) function.…”
Section: Collagen Type II Degradation Products and Comp As Biomarkersmentioning
confidence: 99%
“…Type II collagen peptide was obtained through collagen degradation of type II collagenase enzyme. C-telopeptides of type II collagen (CTX-II) are degradation products of joint tissues, particularly after the destruction of articular cartilage and cartilage extracellular matrix [12]. Therefore, CTX-II is considered to be a potential biomarker for cartilage destruction and to predict OA progression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CTX-II is considered to be a potential biomarker for cartilage destruction and to predict OA progression. [12]. A recent study showed that the development of CTX-II was closely related with knee OA [13].…”
Section: Introductionmentioning
confidence: 99%